PENGARUH TINDAKAN SUPERVISI, PENGALAMAN KERJA, KOMITMEN ORGANISASI, DAN KOMITMEN PROFESIONAL TERHADAP KEPUASAN KERJA AUDITOR - Wiguna, I Made Angga; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi; Vol 16 No 1 (2016), 2016)
The purpose of this study was to determine the effect of supervise action, work experience, organizational commitment and professional commitment to job satisfaction auditor. This research was carried out on the existing public accounting firm in Denpasar. Data collected through questionnaires. The analysis technique used is multiple linear regression. The analysis found that the supervise action, work experience, organizational and professional commitments were significant and positive effect on auditor’s job satisfaction simultaneously. Work experience, organizational commitment and professional commitment partially were positive and significant impact on job satisfaction, while the supervise action were not partial effect on job satisfaction in auditors of the public accounting firm Denpasar.
Keywords: supervision, experience, organizational and professional commitments, job satisfaction